2021
DOI: 10.1371/journal.pone.0260582
|View full text |Cite|
|
Sign up to set email alerts
|

Examining relationships between sleep posture, waking spinal symptoms and quality of sleep: A cross sectional study

Abstract: Introduction Research with a focus on sleep posture has been conducted in association with sleep pathologies such as insomnia and positional obstructive sleep apnoea. Research examining the potential role sleep posture may have on waking spinal symptoms and quality of sleep is however limited. The aims of this research were to compare sleep posture and sleep quality in participants with and without waking spinal symptoms. Methods Fifty-three participants (36 female) were, based on symptoms, allocated to one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…A limited number of physiological and clinical studies have been conducted to test the real effect of HOBE, compared to the supine position, in reducing OSA events, decreasing collapsibility of the mucous membranes, and increasing the upper airway area [ 12 , 15 , 16 , 17 , 18 , 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A limited number of physiological and clinical studies have been conducted to test the real effect of HOBE, compared to the supine position, in reducing OSA events, decreasing collapsibility of the mucous membranes, and increasing the upper airway area [ 12 , 15 , 16 , 17 , 18 , 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…The pathophysiology of OSA is complex and is related to the interplay of both anatomical and non-anatomical factors, including neuromuscular responsiveness, ventilatory instability, and arousal threshold [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ]. All these aspects should be considered in the genesis of POSA patients and could be related to the positive effect of the HOBE position.…”
Section: Discussionmentioning
confidence: 99%
“…Poor sleep quality not only affects productivity and academic performance, but may also lead to injury and car accidents [ 4 ]. Sleep postures are closely related to sleep quality and disorders [ 5 ], and an analysis of sleep posture changes have been used to identify the deep sleep stage [ 6 ]. It was reported that individuals with poor sleep quality spent more time in provocative poses with more frequent posture changes [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Sleep postures are closely related to sleep quality and disorders [ 5 ], and an analysis of sleep posture changes have been used to identify the deep sleep stage [ 6 ]. It was reported that individuals with poor sleep quality spent more time in provocative poses with more frequent posture changes [ 5 ]. While sleep aims to relieve the fatigue of muscles and ligaments, a side-lying posture accompanied by poor support may lead to a sagging spine and sinking lumbar, resulting in sleep-related musculoskeletal problems, such as neck and back pain [ 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…44].At the beginning of the complaint[45], she avoided lying on the right side, but as soon as she enters "nREM", her body moves towards the preferred sleeping position, later awakening with paraesthesia and pain, as it is referred to occur by some authors[18,46]. But after a month, she couldn't even lie on her left side because she started to feel the shoulder pain on that side, a finding that is also described in the literature as a natural evolution of the condition when not treated[47,48,49].Gradually, she began to feel functional limitation at work.To make the patient understand and adhere to the intervention, she was explained the possible cause of her Paraesthesia/pain.…”
mentioning
confidence: 99%